Technology on E-Payment Systems - E S Soegoto; R A Rahman (Universitas Komputer Indonesia, 2021)
The purpose of this study is to examine the importance of technology in business, especially in terms of transactions. The method used in this study was a descriptive method by reading from various international and domestic journals. The results of this study were identification of how simple and important technology was in influencing payment systems that were slowly changing from conventional to electronic payments (e-payment). We also discussed what information related to e-payment, such as safety, functions, and available features from using this e-payment system.